Fatty Acids Derivatives From Eukaryotic Microalgae, Pathways and Potential Applications - Blasio, Martina; Balzano, Sergio (Frontiers in Microbiology, 2021)
The exploitation of petrochemical hydrocarbons is compromising ecosystem and human health, and biotechnological research is increasingly focusing on sustainable materials from plants and, to a lesser extent, microalgae. Fatty acid derivatives include, among others, oxylipins, hydroxy fatty acids, diols, alkenones, and wax esters. They can occur as storage lipids or cell wall components and possess, in some cases, striking cosmeceutical, pharmaceutical, and nutraceutical properties. Long chain (> 20) fatty acid derivatives mostly contain highly reduced methylenic carbons and exhibit a combustion enthalpy higher than that of C14-20 fatty acids, being potentially suitable biofuel candidates. Finally, being the building blocks of cell wall components, some fatty acid derivatives might also be used as starters for the industrial synthesis of different polymers. Within this context, microalgae can be a promising source of fatty acid derivatives and, in contrast with terrestrial plants, do not require arable land neither clean water for their growth. Microalgal mass culturing for the extraction and the exploitation of fatty acid derivatives, along with products that are relevant in nutraceutics (e.g. polyunsaturated fatty acids), might contribute in increasing the viability of microalgal biotechnologies. This review explores fatty acids derivatives from microalgae with applications in the field of renewable energies, biomaterials and pharmaceuticals. Nannochloropsis spp. (Eustigmatophyceae, Heterokontophyta) are particularly interesting for biotechnological applications since they grow at faster rates than many other species and possess hydroxy fatty acids and aliphatic cell wall polymers.